2020
DOI: 10.1093/cid/ciaa238
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy and Detection of High-grade Cervical Intraepithelial Neoplasia (CIN2+) at Post-CIN Management Follow-up Among Women Living With Human Immunodeficiency Virus: A Systematic Review and Meta-Analysis

Abstract: Background We evaluated the association of antiretroviral therapy (ART), CD4+ count and human immunodeficiency virus (HIV) plasma viral load (PVL) on high-grade cervical intraepithelial neoplasia (CIN2+) detection at follow-up after CIN management among women living with HIV (WLHIV). Methods Medline, Embase, Global Health, and PubMed were searched from 1 January 1996 to 15 January 2020. Eligible studies investigated the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…24 Our cohort of treated women has been very rigorously evaluated with HPV detection test combined with colposcopy at follow-up and the follow up duration (median IQR 3.1, 95% CI 2.6-3.7) was longer than most of the studies evaluating treatment of CIN 2/3. 25 Among the HPV positive women at baseline treated for CIN 1 with thermal ablation, 11.8% women in our cohort progressed to a higher grade abnormality. Complete regression of disease on colposcopy and histopathology was observed in 65.6% of the HPV positive WHIV who had high-grade CIN and were treated with thermal ablation.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…24 Our cohort of treated women has been very rigorously evaluated with HPV detection test combined with colposcopy at follow-up and the follow up duration (median IQR 3.1, 95% CI 2.6-3.7) was longer than most of the studies evaluating treatment of CIN 2/3. 25 Among the HPV positive women at baseline treated for CIN 1 with thermal ablation, 11.8% women in our cohort progressed to a higher grade abnormality. Complete regression of disease on colposcopy and histopathology was observed in 65.6% of the HPV positive WHIV who had high-grade CIN and were treated with thermal ablation.…”
Section: Discussionmentioning
confidence: 68%
“…In the high-income countries, ART with adequate control of HIV (HIV PVL <50 copies/ml) was shown to reduce the subsequent risk of CIN 2+ disease but the same was not seen in low-and middle-income countries. 25 The strongest risk factor for CIN 2 or worse disease was persistent HPV infection. Women who cleared HPV infection were also at a substantial risk of developing CIN 2+ lesions.…”
Section: Discussionmentioning
confidence: 99%
“…No other studies included re-screening measures. Furthermore, our cascade focuses on WLHIV and assessing the full continuum of care for this high-risk group offers insights into their specific screening needs and may allow more riskstratified approaches to be developed in the future [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of residual or recurrent cervical disease is higher in WLHIV if they are treated with cryotherapy instead of LEEP [34,35], and also when the excision is incomplete [36,37], but post-treatment follow-up recommendations do not vary by treatment modality. ART status and immunodeficiency may also be associated with differences in CIN treatment outcomes [31]. The relatively low screening test accuracy of VIAC may account for over-treatment and persistent false-positive tests at re-screening [38].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing HIV women with treatment failure and those without, we observed that shorter duration of cumulative undetectable HIV VL, or VL > 50 copies/ml at the time of HSIL treatment, higher maximum VL between time of HIV diagnosis and cervical excision, a lower CD4/CD8 ratio, lower nadir CD4 count and lower CD4 count at time of dysplasia were associated with higher rates of treatment failure. Atemnkeng et al [ 15 ] evaluated the association between cART, viral load, CD4 count and detection of CIN 2 + at follow-up. They observed that cART intake was associated with a reduced risk of CIN 2 + detection at follow-up, after excisional procedures, but not after ablative treatment, as well as in cART users with undetectable VL.…”
Section: Discussionmentioning
confidence: 99%